02.06 Ccr6 modulates severity of arthritis in T cell dependent manner. (1st March 2017) - Bonelli, Michael; Puchner, Antonia; Goeschl, Lisa; Hayer, Sylvia; Niederreiter, Birgit; Smolen, Josef S; Scheinecker, Clemens; Blueml, Stephan
Abstract : Backgrounds and objectives: Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease, driven by the infiltration of various cell types. Evidence suggests that chemokines are involved in a variety of immunological and inflammatory responses. Increased production of MIP-3-α and accumulation of CCR6 expressing mononuclear cells could be found in joints of RA patients. CCR6 is also expressed in human osteoblasts. However, CCR6 expression has also been reported in CD4 + T cells, in particular regulatory as well as Th17 cells. Recent data suggest that CD25 - Foxp3 + T cells express CCR6 and have osteoclastogenic potential. Therefore we investigated which CCR6 expressing cell type is involved in the pathogenesis of arthritis using different arthritis models. Materials and methods: Clinical as well as histological signs of arthritis were investigated in the collagen-induced arthritis (CIA), K/BxN serum transfer arthritis and in the human tumour necrosis factor (hTNFtg) arthritis model, comparing wt and CCR6-/- mice. We analysed the phenotype of lymph node cells by flow cytometry and cytokine concentrations in serum. Anti-collagen antibodies and cytokines were measured by enzyme-linked immunosorbent assay. Results: Since CCR6 is an important component of the innate immune system we compared the development of arthritis in CCR6-/- mice in 2 different arthritis models, known to be T cell independent. Contrary to expectations, no difference could be detected in clinical signs of inflammation as well as in joint histomorphology. In line with this, we could not see differences in bone density between wt and CCR6-/- mice. To investigate the role of CCR6 as part of the adaptive immune system in the development of arthritis we induced CIA in wt and CCR6-/- mice. Surprisingly CCR6-/- mice were completely protected from arthritis. Analyses of different T cell subsets by flow cytomtry revealed a significant reduction of CD25 - Foxp3 + cells. Conclusions: These data suggest that CCR6 expression on T cells is a major driver of arthritis and confirm the pathologic importance of CCR6 expression in T cells. CCR6 as part of the adaptive immune system outcompetes its importance as part of the innate immune system.